The tentmaking pastor : the joy of bivocational ministry - Bickers, Dennis W., 1948- (Grand Rapids, Mich. : Baker Books, 2000)
The author has worked in a factory and now runs a family business while serving a church with under fifty members. Drawing on his experience, he offers practical tips on preparing sermons, furthering your education, setting priorities, and finding balance in your Christian life as a pastor, family member, and employee. Whether you are already a bivocational pastor or are considering it, you will find encouragement and inspiration in this book. --from back cover.
The author has worked in a factory and now runs a family business while serving a church with under fifty members. Drawing on his experience, he offers practical tips on preparing sermons, furthering your education, setting priorities, and finding balance in your Christian life as a pastor, family member, and employee. Whether you are already a bivocational pastor or are considering it, you will find encouragement and inspiration in this book. --from back cover
Includes bibliographical references (pages 131-136).
Keywords: Clergy -- Secular employment